The Illocutionary Acts of Environmental Persuasion in U.S. Online Newspaper Opinion Articles - Dewi, Diana (Widya Mandala Catholic University Surabaya, 2019)
Persuasion, especially in written form, has been acknowledged by scholars as difficult. Success in its attempt requires complex use of, among others, pragmatics. Persuasive texts have therefore been highly researched using the speech act theory. However, a research gap existed for a study of illocutionary acts in newspaper opinion articles. To fill the gap, the current study did a qualitative textual analysis on 10 U.S. online newspaper opinion articles that talk about climate change. The analysis was conducted to discover types of illocutionary acts and persuasive strategies the writers use to successfully persuade readers. It was then found that the writers predominantly performed assertives. The second most frequently used were directives. The most preferred subtypes under these categories were, among others, informing, urging, assuring, and demanding. These preferences further revealed the writers’ persuasive strategies. The strategies were as follows: being highly implicit, being occasionally explicit, giving more information about the issue, conveying certainty and uncertainty, arousing fear, also creating a sense of urgency. These acts and strategies, according to existing theories, could increase the texts’ persuasiveness. Hence, this study establishes that when used in persuasive texts, the previously mentioned illocutionary acts and strategies can help writers to attain persuasion.